Late-Onset Asthma: A Review - Moelamsyah, Yandi Noer; Yunus, Faisal; Nurwidya, Fariz; Amien, Bagus Radityo (Faculty of Medicine Universitas Airlangga, 2024)
Asthma is a chronic respiratory condition with a growing global prevalence, affecting millions of individuals annually. While asthma can develop at any age, late-onset asthma is a specific phenotype that begins in adulthood, as recognized by the Global Initiative for Asthma (GINA) in its 2024 guidelines. This form of asthma is often associated with several predisposing factors, including gender, obesity, occupational exposure, rhinitis, respiratory infections, smoking, stress, and diminished lung function. Unlike early-onset asthma, which frequently involves a history of allergies, late-onset asthma tends to lack allergic triggers, making it a distinct and challenging form of the disease. Managing late-onset asthma is often more complex, as it typically requires higher doses of corticosteroids and demonstrates a reduced responsiveness to standard steroid treatments. The exact mechanisms and pathophysiological processes contributing to the increased severity and poorer clinical outcomes in late-onset asthma remain largely unclear. This uncertainty often leads to underdiagnosis and inadequate management, further complicating patient care. Phenotypic analysis is recommended to improve treatment outcomes. This includes assessing clinical features and utilizing biomarkers, such as inflammatory markers and immunoglobulin E (IgE) levels, to guide targeted therapy when conventional steroid treatments are insufficient. However, there is a significant need for further research to elucidate the underlying mechanisms of late-onset asthma. This literature review is essential to develop more effective, personalized treatment strategies that can address the unique challenges posed by this asthma phenotype, ultimately leading to better management and improved patient outcomes.